DEVELOPMENT OF E-MODULES BASED ON 2P3 LEARNING MODELS TO IMPROVE STUDENTS' MASTERY OF CONCEPTS IN VIBRATION AND WAVE MATERIALS (RESEARCH STUDY AT MTS AL-HUDA, GORONTALO CITY) - Paputungan, Natasya; Yusuf, Frida Maryati; Buhungo, Trisnawaty Junus (Universitas Bhinneka PGRI, 2025)
The importance of learning resources during the learning process is as a channel for information or material conveyed by educators to students. One learning resource that can be used is Ber2p3-based electronic learning modules (E-modules). The objectives of this research are 1) To find out the validation of the e-module based on the Ber2P3 learning model on vibration and wave material?; 2) Knowing the practicality of e-modules based on the Ber2P3 learning model on vibration and wave material?, and; 3) Find out the effectiveness of the e-module based on the Ber2P3 learning model on vibration and wave material? The development procedure used in this research is the Borg and Gall (1989) development model which consists of 10 steps (research and information collection, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision , operational field testing, final product revision, dissemination and implementation). The research sample was 22 class VII students at MTS Al-Huda, Gorontalo City, Gorontalo Province. The research results show that the E-module based on the Ber2p3 learning model meets the feasibility of the learning module. In terms of validity, it meets the criteria of being very feasible with a percentage of 90.97%. In terms of practicality, it meets the very good criteria with a percentage of 82.00%. In terms of effectiveness, it meets the very good criteria with a percentage of 85.71%. Apart from that, based on the analysis of learning outcomes, it is included in the medium criteria range with a percentage N-Gain value of 61.76%.Keywords: Electronic Module; Ber2p3 Learning Model; Borg and Gall Development Model